Study of Amylum Potential as Natural Binders in Hot Briquetting Process in order to Convert Municipal Solid Waste into Solid Fuel - Ilham Utama, Arash
Municipal solid waste has low calorific value. Torrefaction is heat treatment process to increases calorific value of Municipal Solid Waste. However, Torrefaction products are brittle and have low bulk density characteristics that causing problem in handling, transportation and storage. Briquetting using amylum as a binder is a solution to solve these problems. The way to know the role of amylum as binder is briquetting at low pressure with rice as binder and torrefied orange peel as glued object. The parameters of amylum as binder in briquetting process discussed in this study were the mass composition of rice in briquette, briquetting temperature and rice torrefaction temperature. The briquette strength was measured by drop shatter test method. Experiment results showed that the mechanical strength of briquette was proportional to the mass composition of rice and briquetting temperature, but inversely proportional to rice torrefaction temperature. Based on the results of the experiment, the optimum rice mass composition in briquettes was 20%. Rice acts effectively as binder if it is more softened or melted at high briquetting temperature of 200 °C. The optimum rice torrefaction temperature was 150 °C which produces rice with the highest binder performance. These optimum parameters produce briquettes with Drop Shatter Index of 79.87% and calorific value of 6082 kkal/kg.